Sex differences and the role of IL-10 in ischemic stroke recovery. Issue 1 (December 2015) - Conway, Sarah; Roy-O'Reilly, Meaghan; Friedler, Brett; Staff, Ilene; Fortunato, Gilbert; McCullough, Louise
Abstract Females experience poorer recovery after ischemic stroke compared to males, even after controlling for age and stroke severity. IL-10 is an anti-inflammatory cytokine produced by T regulatory cells and Th2 CD4+ helper T cells. In ischemic stroke, an excessive IL-10 response contributes to post-stroke immunosuppression, which worsens outcomes. However, it is unknown if sex differences exist in IL-10 levels after ischemic stroke. In this study, we found that higher levels of IL-10 were associated with poor acute and long-term outcomes after ischemic stroke in female patients but not in males. After controlling for confounders, IL-10 was not an independent predictor of functional outcomes. This suggests that higher serum IL-10 levels may reflect factors that interact with sex such as age and stroke severity.